Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Provide non-trivial solution of the following:

$$\frac{a}{b+c}=\frac{b}{c+a}=\frac{c}{a+b}$$

$a=?, b=?, c=?$

The solution should be general.

share|improve this question

closed as off-topic by alexqwx, Ivo Terek, TooTone, hardmath, Jack D'Aurizio Aug 15 at 1:16

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – alexqwx, Ivo Terek, TooTone, hardmath, Jack D'Aurizio
If this question can be reworded to fit the rules in the help center, please edit the question.

    
What about $a=0$, $b=7$, $c=7$? Do you need all solutions? –  Lior B-S Aug 14 at 10:23
    
yes, i need all solutions not specific but general. –  xclassmechluv Aug 14 at 12:43
    
I would suggest you editing the question... –  Lior B-S Aug 14 at 16:38
1  
@LiorB-S, $0 = 1 = 1$ ? –  MikeDan Aug 14 at 19:57

4 Answers 4

up vote 6 down vote accepted

Here is how you proceed from Nilan's system of equations. Write down the system in matrix form, $\mathbf{A}\mathbf{x}=0$ where $\mathbf{x}=(a,b,c)$ and $\mathbf{A}$ is the matrix of coefficients in terms of $t$.

This is a homogeneous system:

  • if $\mathbf{A}$ is non-singular ($\det \mathbf{A}\neq0$), it has only one solution: the trivial one ($a=b=c=0$);
  • if $\mathbf{A}$ is singular ($\det \mathbf{A}=0$), it has an infinite number of solutions.

We are therefore interested in the case where $\mathbf{A}$ is singular. Work out the determinant of $\mathbf{A}$, which will turn out to be $2t^3+3t^2-1$. Find the roots of this polynomial, which will be $t=-1$ and $t=\frac{1}{2}$.

Solve the system for each of these two cases. You will get:

  1. $t=1$ $\rightarrow$ $a+b+c=0$.

  2. $t=\frac{1}{2}$ $\rightarrow$ $a=b=c$.

These are the general solutions; any setting of $a,b,c$ that does not satisfy one of the above two conditions is not a solution.


More Generality

It turns out that this generalizes to any number of variables, i.e. write the problem as:

$$ \frac{x_i}{\sum x - x_i} = \frac{x_j}{\sum x - x_j} \quad \forall i,j=1,2,\dots,n $$

Then the only solutions are:

  1. $\sum x = 0$;
  2. all $x$'s are equal.

To see this, you can either generalize the linear-algebraic approach above (see here), or more simply, look at the problem formulation and realize that either all the denominators must be identical (which corresponds to Condition 1) or $\sum x = 0$ so that the (magnitudes of the) denominators cancel out with the numerators for all $i$'s.

share|improve this answer
    
Wonderfull!!!!!!!!!! –  Nilan Aug 15 at 9:21
    
@MGA more generality i didn't understand. I accepted your answer for the first half. The graphical solution of the problem is a plane. –  xclassmechluv Aug 19 at 9:15
    
@xclassmechluv By "more generality" I mean: extend your pattern to the case of not just $3$ ($a,b,c$), but $n$ variables ($x_1,x_2,\dots,x_n$). We notice that the denominator is the sum of all the variables except the numerator, so we can write it as (sum of all variables) - (numerator). It turns out that when you formulate the problem for $n$ variables, (a) the solutions for the case of $n=3$ still apply; and (b) it is actually easier to see both solutions intuitively (at least for me). –  MGA Aug 19 at 16:30

HINT:

$\displaystyle\frac{a}{b+c}=\frac{b}{c+a}=\frac{c}{a+b}=\frac{a+b+c}{b+c+(c+a)+(a+b)}$

Similarly, $\displaystyle F=\frac{a}{b+c}=\frac{b}{c+a}=\frac{a-b}{b+c-(c+a)}$

Either $a=b$ or $\displaystyle F=-1$

Hope these should help

share|improve this answer

$$\dfrac{a}{b+c}=\dfrac{b}{c+a}=\dfrac{c}{a+b}=t$$ Then $$-a+bt+ct=0$$ $$at-b+ct=0$$ $$at+bt-c=0$$ Try to solve them. This would be a help for you.

share|improve this answer
    
i tried this already but is not generalized approach. –  xclassmechluv Aug 14 at 12:44
2  
@xclassmechluv Why not? Note that $t$ is a free parameter. –  MGA Aug 14 at 12:50
    
@xclassmechluv, mathworld.wolfram.com/CramersRule.html –  lab bhattacharjee Aug 14 at 16:57

Besides to the good answers posted for this question (this answer and this one), I think finding eigenvalues and eigenvectors of such system will help you to find the solution.

$$\begin{array}{l}\frac{a}{{b + c}} = \frac{b}{{c + a}} = \frac{c}{{a + b}} = t\\\left[ {\begin{array}{*{20}{c}}1&{ - t}&{ - t}\\{ - t}&1&{ - t}\\{ - t}&{ - t}&1\end{array}} \right]\left[ {\begin{array}{*{20}{c}}a\\b\\c\end{array}} \right] = \left[ {\begin{array}{*{20}{c}}0\\0\\0\end{array}} \right]\\\left[ C \right]\left\{ X \right\} = \left\{ 0 \right\}\\\det \left[ {C - \lambda I} \right] = 0\\\det \left[ {\begin{array}{*{20}{c}}{1 - \lambda }&{ - t}&{ - t}\\{ - t}&{1 - \lambda }&{ - t}\\{ - t}&{ - t}&{1 - \lambda }\end{array}} \right] = 0\\\left( {1 - \lambda } \right)\left\{ {{{\left( {1 - \lambda } \right)}^2} - {{\left( { - t} \right)}^2}} \right\} = 0\\\lambda = 1,1 - t,1 + t\\\begin{array}{*{20}{c}}{\lambda = 1}\\{\lambda = 1 - t}\\{\lambda = 1 + t}\end{array}\left| {\begin{array}{*{20}{c}}{ + \left( {1 - \lambda } \right)a - \left( t \right)b - \left( t \right)c = 0}\\{ - \left( t \right)a + \left( {1 - \lambda } \right)b - \left( t \right)c = 0}\\{ - \left( t \right)a - \left( t \right)b + \left( {1 - \lambda } \right)c = 0}\end{array}} \right\rangle \left\{ {\left. {\begin{array}{*{20}{c}}{a = b = c = 0}\\{a = b = c = 0}\\{a + b + c = 0}\end{array}} \right\rangle } \right.\left. {\underline {\, {a + b + c = 0} \,}}\! \right| \end{array}$$

As it seems the answer is compatible with the other answers to this question.

share|improve this answer

Not the answer you're looking for? Browse other questions tagged or ask your own question.